Micro-topographies formed by erosion can drive seedling emergence by rebuilding micro-habitats on weathered waste dumps in northeastern China - Wang, Dongli; Qiao, Jingting; Zhang, Ye; Liao, Mingji; Wang, Dong; Zhao, Xiaoliang; Qiao, Yan (Frontiers in Earth Science, 2023)
Restoring vegetation on waste dumps is imperative as soil erosion heavily impacts these areas and creates erosion micro-topographies, including bare slopes, rills, ephemeral gullies, and deposit bodies. These micro-topographies may affect seedling emergence by forming special micro-habitats, while the mechanism is vague. This study determined the substrate chemical (pH and electrical conductivity) and physical (capillary porosity, capillary water content, and mechanical composition) properties in different micro-topographies. In addition, the temporal dynamics of micro-climates (air temperature and air humidity), substrate hydrothermal conditions (substrate temperature and water content), and seedling emergence were investigated. We then used The redundancy analysis (RDA), random forest (RF), and receiver operating characteristic (ROC) curve analysis were then used to identify the main factors affecting seedling emergence and clarify the relationships among environmental conditions. Our results demonstrated that seedling densities in the rill, ephemeral gully, and deposit body were 1.78 times, 3.42 times, and 3.97 times higher than on the bare slope. More species were found in the rill, ephemeral gully, and deposit body (Artemisia annua, Salsola collina, Setaria viridis, and Tribulus terrestris) than on the bare slope (Salsola collina). The main factors affecting seedling emergence were air humidity, substrate temperature, and substrate water content. The mechanical composition may have affected substrate water content during the initial stage of seedling emergence and substrate temperature during the entire period. We demonstrated that the ephemeral gully and deposit body might provide micro-habitats with a lower substrate temperature and higher substrate water content favorable to seedling emergence, thus, guiding vegetation restoration on waste dumps or other disturbed areas.